Evaluation of Serum Adipokines in Peripheral Arterial Occlusive Disease - Gherman, Claudia D. (Hindawi Publishing Corporation, 2012)
Aim. Out study aimed to assess the serum levels of adipokines in patients with peripheral arterial occlusive disease (PAOD) caused by atherosclerosis. Methods. Serum samples were obtained from 221 patients. One hundred and forty patients, (26 females and 114 males) met the inclusion criteria and were assigned into the case group. Eighty one patients (17 females and 64 males), were included in the control group. Circulating plasma levels of adiponectin, leptin, resistin, and TNF-α were measured using the enzyme-linked immunosorbent assay (ELISA) method. Results. Significant lower levels of adiponectin were present (P = 0.0061) in PAOD patients (2380.23 ± 1634.42 pg/mL) compared to the control group (3065.06 ± 1901.2 pg/mL). The mean value of leptin (2844.42 ± 3301.08 pg/mL) and resistin (2047.81±3301.08 pg/mL) patients included in the PAOD group was higher, as compared to the control group. Statistically significant difference was found between the two groups for leptin (P = 0.0332) and for resistin (P = 0.0352). No statistically significant difference for TNF-α was found between the two groups (P > 0.05). Conclusion. The markers of inflammation secreted by the adipose tissue (adiponectin, leptin, resistin) showed significant differences in patients from the case group (with PAOD) compared to the control group.